SIG para regularização fundiária em faixa de fronteira - Oliveira Filho, José Antonio Teixeira de (2023)
The migration of work procedures from analog to digital environment in the Federal Public Service has become a necessity in recent years and the lack of financial resources is no longer a barrier to the use of technology because of the possibility of developing solutions in the institutions themselves. Thus, this research paper proposes a way to answer the question: "How to reformulate the procedure for searching and making available the information present in INCRA-PR's land collection? INCRA is a federal autarchy that operates in the state of Paraná through a regional superintendence and an advanced unit and is responsible, among other activities, for landholding regularization on the border strip. The execution of such action produces, throughout time, documents that are filed in paper and that are important both for the use of the society in general and for internal use, because they are documents of property of a rural area. The general objective is to propose the modernization of INCRA-PR's land collection to digitalize the access to information related to its activities. To this end, a systematic literature review was carried out, first to identify the use of GIS in the Brazilian Public Service. Then, to get to know the reality of INCRA's SRs and identify the use of geotechnologies in the execution of landholding regularization, a data collection through the application of a questionnaire was carried out with the eleven regional superintendencies that perform this same activity, as well as the mapping of the procedure of storage and search of documents in the collection of the Advanced Unit Iguaçu, in the city of Cascavel-PR. The intended change is based on the use of empirical data from the local government structured in a GIS, based on a geographic database modeled on open-source technology. The cartographic base was edited in QGIS software, and the database was elaborated in the PostgreSQL platform, with its spatial extension PostGIS. A Web Map was also developed to search and make available the documents present in the land books. As contributions of this work, we can mention the production of data regarding the use of GIS by the public administration in the last years and the unknown information within the autarchy regarding its own structure and procedures. Another contribution was the development of a solution for the modernization of a process common to several superintendencies and that can be replicated, according to the needs or characteristics of each state. The study found shortcomings and good practices, which brings grounds for future research regarding work procedures and the use of geospatial tools, which can contribute to the performance of the activities inherent to INCRA.